The Effect of Isometric Handgrip and Isometric Leg Muscular Contractions on Resting Blood Pressure and Arterial Distensibility in Persons Medicated for Hypertension - Visocchi, Adrienne (My University, 2004)
Hypertension and reduced arterial distensibility are independent risk factors for cardiovascular disease. Previous research has found that isometric training reduces resting blood pressure (RBP) (Wiley et al. 1992; Taylor et al. 2003) yet the mechanisms responsible remain elusive. Improved arterial distensibility may contribute to this reduction in RBP. The purpose of the present study was threefold: 1) to replicate the RBP lowering effect of isometric handgrip (IHG) exercise; 2) to compare IHG and isometric leg press (ILP) based in their RBP lowering effects; and 3) to determine if central or peripheral arterial distensibility improved with IHG or ILP. The population examined was people whom were medicated for hypertension.
RBP, as assessed by brachial oscillometry, and arterial distensibility, as assessed by Doppler ultrasound and applanation tonometry in the carotid, brachial and femoral arteries, were measured pre training, after 4 weeks of training, and post training. Participants performed unilateral IHG exercise (n=10) or ILP exercise (n=9) 3 times/week for 8 weeks at 30% MVC or acted as a non-exercising control group (n=5).
Results indicated that the present study was unable to reproduce the RBP reductions noted in previous studies using IHG exercise. Also, the ILP exercise group did not experience reductions in RBP. Finally, neither central nor peripheral arterial distensibility improved in the IHG or ILP group when compared to the control group.
Although these findings are contrary to our hypotheses one must consider that the control group examined contained very few subjects. This may have limited our ability to detect statistically significant changes in RBP and arterial distensibility.
Keywords: isometric handgrip, leg exercise, resting blood pressure, arterial distensibility, hypertension, cardiovascular disease